Rigid polyurethane foam from glycolysed polyethylene terephthalate dissolved in palm-based polyol - Khairiah Haji Badri,; Ly Iliyana Mohd Dawi,; Nur Ashikin Abd Aziz, (Universiti Kebangsaan Malaysia, 2013)
An investigation on the thermal and mechanical properties of rigid polyurethane (PU) foam from polyethylene terephthalate (PET) waste (of plastic drinking bottles) was conducted. The PET waste was glycolysed with ethylene glycol prior to blending with palm based-polyol (PKO-p). This blend was then reacted with 2, 4-methylene diphenyl diisocyanate (MDI) at a ratio of 1:1 to form the PU foam. The incorporation of the glycolysed PET (g-PET) into the PKO-p was studied at 50, 70 and 100% w/w loading. PU foam prepared from 100% w/w g-PET (without PKO-p) resulted in PU with high glass transition temperature and mechanical strength. This water-blown foam has molded and core densities of 182 kg m-3 and 179 kg m-3, respectively, with maximum compressive stress and modulus at 396 kPa and 1920 kPa, respectively. An initial enthalpy value of 3164.8 cal g-1 and a glass transition temperature of 65ºC were observed.